(untitled) (American Journal of Islam and Society, 2006)
Since its first release in 1977 by Oxford University Press, Quranic Studies has become part of a wider body of published scholarship that is taking a fresh look at the traditional renditions of early Islamic history. Apart from this book, John Wansbrough (1928-2002), who was professor of Semitic Studies at London’s School of Oriental and African Studies (SOAS), also wrote The Sectarian Milieu (Oxford University Press: 1978). Others have since continued to research the formative period of Islam in a similar fashion. Among the most controversial contributions in this genre was Hagarism: The Making of the Islamic World (Oxford University Press: 1977), a joint project of Patricia Crone (who did her Ph.D. under Wansbrough) and Michael Cook (who also taught at SOAS until 1986).The scholars belonging to this “school” of history writing have been characterized as representatives of a “renewed scepticism” (Mohammed Arkoun), “revisionists” (R. Stephen Humphreys), and even practitioners of “bad Orientalism” (Leonard Binder). This last characterization is indicative of the direction in which the discussions have moved. Rather than having a continued exchange of views informed by scholarly arguments, which this highly specialist and arcane subject matter would certainly merit, the debate was, regrettably, soon dominated by ideological overtones. Due to new communication technologies, it became part of a discourse that went far beyond what would have been its normal readership. Now, Quranic Studies has been released again, enhanced with a foreword, new annotations, and a glossary by Andrew Rippin, a Qur’anic studies expert from Victoria University in Canada. Rippin undertook this venture in order to counter some of the ideological and non-scholarly ways in which the book has been used during the first twenty-five years of its existence. In fact, the editor even questions whether all of those voicing the strongest opinions about this book have actually ever read it. That would indeed be most remarkable, because Wansbrough’s study is at a level of erudition that few can hope to master. Unfortunately, that is also its main drawback: For the non-specialist, and by that I mean the Islamicist whose interests lie outside scriptural exegesis, this erudite book poses a ...